Analysis of Tools for The Description and Analytical Processing of Enviromental Data - Ragimova N.A; Abdullayev V.H.; Khalilov M.E.; Abuzarova V.A.; Askerov T.K. (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
The objects of the research are tools that support the description and analytical processing of environmental data requests. These tools are used for environmental monitoring. Analytical processing of environmental data is necessary for this monitoring by the persons concerned. Here, a star schema is used to describe the data. Analytical data processing tools are required for analysis and research of environmental data. The results of analytical processing of environmental data are used to speed up decision-making. This article also describes the structure of the analytical data processing tool. Therefore, one of the problem points is how to describe the data. For this purpose, an environmental data relay scheme is defined, and the data description is implemented in multidimensional cubes. Due to the growth of data volume, data processing is carried out using multi-dimensional visualization methods. In addition, a visual user interface has been created for analytically processing queries based on scale data. The result of this research is to find a method for describing environmental data. At the end of the research, a hypercube was obtained, with the help of which it was possible to structure environmental data and carry out analytical processing of them. To this end, environmental data have been described using a multi-dimensional visualization method. And OLAP technologies were used to carry out analytical processing of this data. OLAP technologies allow aggregate data to be used and presented as a hypercube. The results of the research can be used as a basis for an environmental information system that is used for environmental monitoring.